Occurrence of COVID-19 in cystic fibrosis patients: a review - Abolhasani, Fatemeh Sadat; Moein, Masood; Rezaie, Niloofar; Sheikhimehrabadi, Parimah; Shafiei, Morvarid; Afkhami, Hamed; Modaresi, Mohammadreza (Frontiers in Microbiology, 2024)
Cystic fibrosis (CF) is a genetic ailment resulting from mutations within the cystic fibrosis transmembrane conductance regulator (CFTR) gene. This autosomal recessive disorder is characterized by way of diverse pathobiological abnormalities, such as the disorder of CFTR channels in mucosal surfaces, due to the inadequate clearance of mucus and sputum, in addition to the malfunction of mucous organs. However, the number one motive of mortality in CF sufferers is pulmonary failure, which is attributed to the colonization of opportunistic microorganisms, the formation of resistant biofilms, and the subsequent decline in lung characteristics. In December 2019, the World Health Organization (WHO) declared the outbreak of the radical coronavirus sickness 2019 (COVID-19) as a worldwide public fitness crisis, which unexpectedly spread not only within China but also globally. Given that the respiration gadget is the primary goal of the COVID-19 virus, it is crucial to investigate the impact of COVID-19 on the pathogenesis and mortality of CF patients, mainly in the context of acute respiratory distress syndrome (ARDS). Therefore, the goal of this review is to comprehensively review the present literature on the relationship between cystic fibrosis, COVID-19 contamination, and the development of ARDS. Several investigations performed within the early stages of the virus outbreak have discovered unexpected findings regarding the occurrence and effectiveness of COVID-19 in individuals with cystic fibrosis (CF).Contrary to initial expectancies, the rate of infection and the effectiveness of the virus in CF patients are lower in comparison to the overall populace. This may be attributed to different factors, including the presence of thick mucus, social avoidance, using remedies which include azithromycin, the fairly younger age of CF patients, the decreased presence of ACE-2 receptors, and the effect of CFTR channel disorder on the virus's replication cycle and infectivity. However, it's far essential to notice that certain situations, which include undergoing a transplant, can also doubtlessly boost the susceptibility of CF sufferers to COVID-19. Furthermore, as CF sufferers age, it's far vital to keep in mind the prevalence of the SARS-CoV-2 virus in this population.